2014
DOI: 10.1016/j.taap.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of natural, synthetic and environmental estrogens for zebrafish estrogen receptors

Abstract: Zebrafish, Danio rerio, is increasingly used as an animal model to study the effects of pharmaceuticals and environmental estrogens. As most of these estrogens have only been tested on human estrogen receptors (ERs), it is necessary to measure their effects on zebrafish ERs. In humans there are two distinct nuclear ERs (hERα and hERβ), whereas the zebrafish genome encodes three ERs, zfERα and two zfERβs (zfERβ1 and zfERβ2). In this study, we established HeLa-based reporter cell lines stably expressing each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
8
32
0
Order By: Relevance
“…Reports have showed that ERs expression can be induced by diverse estrogens or estrogen analog and different type of ER have a different binding affinity for the different ligands. Using HELN assay, which ERE-driven fulllength zebrafish ERα, ERβ1 and ERβ2 expression in HeLa cells, 4-t-OP has been demonstrated to have greater affinity towards zebrafish ERα and ERβ2 relative to ERβ1 [33]. Our study present higher expression level induced by 4-t-OP in ERα and ERβ2 also potentially suggesting that zebrafish ERα and ERβ2 have higher affinity for 4-t-OP.…”
Section: Discussionsupporting
confidence: 49%
“…Reports have showed that ERs expression can be induced by diverse estrogens or estrogen analog and different type of ER have a different binding affinity for the different ligands. Using HELN assay, which ERE-driven fulllength zebrafish ERα, ERβ1 and ERβ2 expression in HeLa cells, 4-t-OP has been demonstrated to have greater affinity towards zebrafish ERα and ERβ2 relative to ERβ1 [33]. Our study present higher expression level induced by 4-t-OP in ERα and ERβ2 also potentially suggesting that zebrafish ERα and ERβ2 have higher affinity for 4-t-OP.…”
Section: Discussionsupporting
confidence: 49%
“…While research testing the effects of BPA on development are abundant, many of these studies use environmentally-relevant low nanomolar concentrations of BPA in treatment water (Kinch et al, 2015; Kinch et al, 2016; Saili et al, 2012; Wu et al, 2017). Based on our results, the amount of BPA available to the embryo is substantially less than the reported EC 50 of BPA for the zebrafish estrogen receptors ERα, 599 nM, ERβ1, 18.9 μM, and ERβ2, 3.8 μM (Pinto et al, 2014). For example, in 2015, Kinch and colleagues reported altered neurogenesis in embryos exposed to 6.8 nM BPA from 0-5 dpf.…”
Section: Discussionmentioning
confidence: 62%
“…EE2 is a known environmental contaminant that may have adverse effects on aquatic wildlife, particularly during development (Bhandari et al, 2015; Santos et al, 2014; Volkova et al, 2015). Its structural similarity to E2, the primary circulating estrogen in humans, in conjunction with its high affinity for estrogen receptor alpha (ERa)(Pinto et al, 2014), makes EE2 relevant for toxicity assays in aquatic animals as well as animal models of human toxicity and teratogenicity. As a steroidal estrogen, EE2 is assumed to diffuse through cell membranes and be absorbed by lipophilic tissues, such as the embryonic yolk.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that very similar E2‐EQ values were obtained by the 2 bioassays, that is, 0.1 and 0.2 ng E2‐EQ/L for the upstream and downstream sites, respectively, and 0.5 ng E2‐EQ/L for the effluent site. The lack of species‐specific estrogenic response suggests that both assays detected the same active compounds in the samples with similar sensitivity, as they do for steroidal estrogens (Cosnefroy et al ; Pinto et al ). Interestingly, no activity was detected at the 3 sampling points by the ZELH‐zfERα assay, which coincides with the reported lower sensitivity of this assay to steroidal estrogens (Cosnefroy et al ) and to environmental samples (Sonavane et al ) as compared to the MELN or ZELH‐zfERβ2 bioassays.…”
Section: Resultsmentioning
confidence: 91%